Prevalence of pulmonary arterial hypertension in post-tuberculosis lung fibrosis patients: A cross-sectional observational study - Rupak Chatterjee; Priyanka Ghosh; Kumkum Sarkar; Shambo Samrat Samajdar; Shatavisa Mukherjee; Alex George; Netai Pramanik (The Journal of Association of Chest Physicians)
Introduction: Post-tuberculosis (TB) lung fibrosis is an infrequently reported cause of Pulmonary arterial hypertension (PAH). Pulmonary TB still being an important global health problem, especially in developing countries, PAH developing after pulmonary TB deserves attention. This study was undertaken to know the prevalence of PAH among patients with post-TB lung fibrosis. Methods: A cross-sectional observational study was carried out in two tertiary care hospitals in Kolkata over a period of 1 year. Sixty adult post-TB lung fibrosis patients without any cardiovascular or other pulmonary comorbidities were included in this study. Results: Out of the 60 patients with varying degrees of lung fibrosis confirmed radiologically, eight patients were found to have PAH (13.33% of the study population). Among the eight cases, six were males and two were females. Five of the males were smokers with a mean of 17.6 pack years of smoking. Out of the eight diagnosed PAH cases, three were mild PAH, four were moderate, and one case had severe PAH (grading based on 2D echocardiography findings). Pulmonary function test (PFT) revealed obstructive pattern in three cases, restrictive pattern in three cases, and mixed in two cases. On PFT, smokers with PAH exhibited obstructive pattern and mixed pattern, whereas the nonsmoker PAH cases exhibited restrictive pattern. Conclusion: All post-TB lung fibrosis cases must be followed up at regular intervals and screened to rule out PAH. Early diagnosis and prompt treatment of the cases will help to reduce morbidity and mortality of the disease which otherwise has a poor prognosis.